Squamous Cell Carcinoma of the Hilar Bile Duct - Yamana, Ippei (S. Karger AG, 2011)
We herein report a rare case of squamous cell carcinoma of the hilar bile duct. A 66-year-old Japanese male patient was admitted to our hospital because of appetite loss and jaundice. Abdominal computed tomography revealed an enhanced mass measuring 10 × 30 mm in the hilar bile duct region. After undergoing biliary drainage, the patient underwent extended right hepatic lobectomy with regional lymph nodes dissection. The tumor had invaded the right portal vein. Therefore, we also performed resection and reconstruction of the portal vein. Histopathologically, the carcinoma cells exhibited a solid structure with differentiation to squamous cell carcinoma with keratinization and intercellular bridges. Immunohistochemical staining of the tumor cells revealed positive cytokeratin staining and negative CAM 5.2 staining. Based on these findings, a definitive diagnosis of well-differentiated squamous cell carcinoma of the hilar bile duct was made.